Severe but reversible acute kidney injury resulting from Amanita punctata poisoning - Eunjung Kang; Ka-Young Cheong; Min-Jeong Lee; Seirhan Kim; Gyu-Tae Shin; Heungsoo Kim; In-Whee Park (The Korean Society of Nephrology, 2015)
Mushroom-related poisoning can cause acute kidney injury. Here we report a case of acute kidney injury after ingestion of Amanita punctata, which is considered an edible mushroom. Gastrointestinal symptoms occurred within 24 hours from the mushroom intake and were followed by an asymptomatic period, acute kidney injury, and elevation of liver and pancreatic enzymes. Kidney function recovered with supportive care. Nephrotoxic mushroom poisoning should be considered as a cause of acute kidney injury.